Preparation and characterization of lithium based glass ceramic conducting electrolytes / Maziidah Hamidi - Hamidi, Maziidah (2014)
Lithium aluminium titanium phosphate (LATP), Lii+xAIxTi2-x(P0 4 ) 3 (x = 0.0-0.5), lithium based glass ceramics conducting electrolyte with NASICON were successfully prepared by soi gel technique with acetic acid as chelating agent. TGA was carried out to determine the annealing temperature by finding out the precursors’ thermal stability. Lii+xAlxTi2-x(P0 4 ) 3 were annealed at 600°C, 700°C, 800°C and 900'’C for 3 hours in air. XRD revealed major phase of LiTi2(P0 4 )3, which has NASICON structure, exist in all prepared samples with secondary phases TiP2 0 ? and AIPO4. FTIR shows presence of NASICON phosphate peaks from which dominates wavenumber ranged 600 cm’' to 1300 cm’'. Peaks around 1045 cm ', 870 cm"', 740 cm'', and 610 cm'' indicate the presence of NASICON P0 4 ^' in all of the prepared samples. This also confirms the presence of LiTi2(P0 4 ) 3 in all of the samples. The ionic conductivity were analyzed with IS at room temperature and elevated temperature. The highest room temperature conductivity was 2.84 x 10'^ Scm'’ of sample Lii.4Alo4Tii.6(P0 4 )3, (LATP 4), annealed at 800°C for 3 hours in air. The increase in ionic conductivity from LATP 0 annealed at 800°C, 3.12 x 10'^ Scm ' shows that the partial substitution of Al^^ with Ti"*^ was able to increase the ionic conductivity. The high ionic conductivity of LATP 4 was supported by the lower intensity of impurity peaks, as reported in XRD. From ac conductivity analysis using Jonscher’s universal power law, the s values of LATP 4 at various temperatures are within the range 0 < s < 1. It is concluded that the LATP 4 annealed at 800°C followed the quantum mechanical tunneling (QMT) model due to the independency of s to temperature.